Consumer intention to purchase green vehicles in the South African market: A theory of planned behaviour perspective - Brett Hamilton; Marlize Terblanche-Smit (South African Journal of Business Management, 2018)
Background: While alternative fuel vehicles (AFVs) still account for a relatively small percentage of the total vehicle sales, this is set to change as awareness of the impact of car usage on the environment grows among consumers, vehicle-emission controls increase and the number of AFVs available in the market increases.Objective: This study used Ajzen's theory of planned behaviour (TPB) to investigate the role of attitude (A), subjective norm (SN) and perceived behavioural control (PBC) on the intention to purchase AFVs in the South African market and thus empirically testing the hierarchical attitude–behaviour model of consumer behaviour.Method: A quantitative research methodology was followed and a self-administered, Internet-based survey instrument was used to collect data from 196 South African respondents.Results: The findings indicate significant relationships between A (β = 0.61), SN (β = 0.26), and PBC (β = 0.13) and behavioural intention. These findings support literature and emphasise that (1) attitudinal factors have the biggest influence on intention, (2) the perceived support and encouragement of referent others are important considerations for individuals and (3) control factors play a critical role in consumers' decision to purchase an AFV.Conclusion: In order to create effective marketing strategies for AFVs retailers and marketers should focus on the impact of attitude, subjective norm (SN) and perceived behavioural control (PBC) to influence behavioural intention.
Keywords: 650